Contribution of Lofti Asker Zadeh to fuzzy logic - Ameer Amsa, Mohamad Ghazali; Ismail, Ahmad Faris (IIUM Press, 2011)
The objective of this chapter is to highlight the contribution of Lofti Asker Zadeh, the founder of fuzzy logic. Lotfi Zadeh introduced the concept of fuzzy logic through his published paper 'Fuzzy sets' in 1965. The literal meaning of fuzzy is vague, imprecise, subjective or uncertain which gives impression that fuzzy logic is the 'logic' that is fuzzy. However, that assumption is misleading since the actual meaning of fuzzy logic is the logic used to describe fuzziness or imprecise thing (Negnevitsky, 2002, p. 87). Fuzzy logic allows machine to imitate the human thought process, while solving uncertainty problems by means of 'computing with the words' technique. In this technique, all the words by given each of linguistic variables have different degree of membership values (base on human perception) in the fuzzy set. This idea is similar to human decision making technique since used to judge something with linguistic variable such as 'good', 'better' , 'nice' which are uncertain and very subjective because it based on individual perception of something which and thus may differ from one person to another. Fuzzy set theory led to development of various intelligent machines that able to decide the solution in the way more to 'human like manner' which called Intelligent System (IS) to deal with uncertainty and impreciseness of real world problems.